Isolation of endophytic actinomycetes from selected plants and their antifungal activity - Taechowisan T. (2014)
The isolation of endophytic actinomycetes from surface-sterilized tissues of 36 plant species was made using humic acid-vitamin (HV) agar as a selection medium. Of the 330 isolates recovered, 212 were from roots, 97 from leaves and 21 isolates from stems with a prevalence of 3.9, 1.7 and 0.3%, respectively. Identification of endophytic actinomycetes was based on their morphology and the amino acid composition of the whole-cell extract. Most isolates were classified as Streptomyces sp. (n = 277); with the remainder belonging to Microbispora sp. (n = 14), Nocardia sp. (n = 8) and Micromonospora sp. (n = 4). Four isolates were unclassified and 23 were lost during subculture. The most prevalent group of isolates were the Streptomyces sp. occurring in 6.4% of the tissue samples of Zingiber officinale. Scanning electron microscopy investigation of this plant revealed that 7.5% of the root and 5% of the leaf samples contained endophytes. Three of the Streptomyces sp. isolates strongly inhibited Colletotrichum musae, five were very active against Fusarium oxysporum and two strongly inhibited growth of both test fungi.